Clinical Scoring Systems in Predicting the Outcomes of Small Bowel Bleeding - Shual, Su; Zhifang, Zhang; Yuming, Wang; Hong, Jin; Chao, Sun; Kui, Jiang; Bangmao, Wang (Turkish Journal of Gastroenterology, 2021)
Background: The aim was to assess the clinical Glasgow–Blatchford score (GBS), Rockall score (CRS), and AIMS65 score in predictingoutcomes (rebleeding, need for intervention, and length of stay) among patients with small bowel hemorrhage.Methods: We conducted a retrospective study of patients with small bowel bleeding (SBB). Rebleeding, need for intervention, and lengthof stay was investigated by 3 scoring systems. The area under the receiver operator characteristic curve was used to analyze the performanceof 3 scoring systems.Results: Among 162 included patients, the scores of rebleeding, intervention, and length of stay ≥10 days groups were higher than norebleeding, non-intervention, and length of stay <10 days groups, respectively (P < .05). The CRS, GBS, and AIMS65 scoring systems demonstratedstatistically significant difference in predicting rebleeding (AUROC 0.693 vs. 0.790 vs. 0.740; all P < .01), intervention (AUROC:0.726 vs. 0.825 vs. 0.773; all P < .01) and length of stay (AUROC 0.651 vs. 0.631 vs. 0.635; all P < .05). Higher cut-off scores achieved bettersensitivity/specificity [rebleeding (CRS > 2, GBS > 7, AIMS65 > 0); need for intervention (CRS > 2, GBS > 7, AIMS65 > 0); length of stay(CRS > 0, GBS > 7, AIMS65 > 1)] in the risk stratification.Conclusions: The GBS system is reliable to be recommended for routine use in predicting rebleeding and the need for intervention forearly decision making in patients with SBB. The 3 scoring systems are poorly useful in predicting length of stay.